Agricultural market information systems in Africa 3: Identifying clients and planning services - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council; International Fertilizer Development Center (Technical Centre for Agricultural and Rural Cooperation, 2015)
This is one of a series of information sheets for people designing and implementing agricultural market information systems in Africa